2020
DOI: 10.1002/cncr.32887
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer early detection: A phased approach to implementation

Abstract: When breast cancer is detected and treated early, the chances of survival are very high. However, women in many settings face complex barriers to early detection, including social, economic, geographic, and other interrelated factors, which can limit their access to timely, affordable, and effective breast health care services. Previously, the Breast Health Global Initiative (BHGI) developed resource-stratified guidelines for the early detection and diagnosis of breast cancer. In this consensus article from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
258
0
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 416 publications
(285 citation statements)
references
References 58 publications
4
258
0
23
Order By: Relevance
“…As of January 2020, a total of 5 BHGI assessments have been performed in Tanzania, Brazil, Uganda, Panama, and India (Table 3). 39‐47 Assessment reports have included analysis of the questionnaire data as well as data regarding breast cancer mortality and incidence rates (when available), stage distribution from national and regional facilities, and exisiting peer‐reviewed literature concerning breast cancer epidemiology in the country or region. A review of governmental policies, state and private insurance rates versus out‐of‐pocket payments for services, workforce shortages, and health system organization also is included.…”
Section: Methodsmentioning
confidence: 99%
“…As of January 2020, a total of 5 BHGI assessments have been performed in Tanzania, Brazil, Uganda, Panama, and India (Table 3). 39‐47 Assessment reports have included analysis of the questionnaire data as well as data regarding breast cancer mortality and incidence rates (when available), stage distribution from national and regional facilities, and exisiting peer‐reviewed literature concerning breast cancer epidemiology in the country or region. A review of governmental policies, state and private insurance rates versus out‐of‐pocket payments for services, workforce shortages, and health system organization also is included.…”
Section: Methodsmentioning
confidence: 99%
“…Women with breast cancer in LMICs commonly present or are ultimately diagnosed with late‐stage (locally advanced or metastatic) disease 25 . In such settings, efforts to promote early detection are an absolute prerequisite to improving breast cancer outcomes 26 . A 2019 report from Kenya found that key barriers to early detection and treatment included cost, inadequate knowledge, distance to health facilities, communication with health providers, medicine stock‐outs, long waiting periods, limited or no counseling at diagnosis, patient vulnerability, and limited access to rehabilitation options 27 .…”
Section: Breast Health System Requirementsmentioning
confidence: 99%
“…2). 26 Early diagnosis strategies for symptomatic patients are also necessary for the evaluation and workup of patients under the age of 40‐45 years old who are too young to be appropriate screening candidates (even in high‐income settings) 31 …”
Section: Breast Health System Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCCN Guidelines specify appropriate cancer management in the United States and more specifically within the member institution cancer programs, which represent maximal resource settings. In these settings, there should be little or no resource impediment to obtaining the highest level of recommended care, although significant socioeconomic barriers continue to exist that prohibit access to care among vulnerable sectors of society 6,7 …”
Section: Introductionmentioning
confidence: 99%